2013
DOI: 10.1111/apa.12241
|View full text |Cite
|
Sign up to set email alerts
|

Screening for coeliac disease in preschool Greek children: the feasibility study of a community‐based project

Abstract: This protocol using rapid immunochromatographic test for the detection of both IgA deficiency and CD is easy to be performed by nonmedical staff in a community setting, enabling the accurate identification of new CD cases among asymptomatic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
(24 reference statements)
1
13
0
6
Order By: Relevance
“…Karagiozoglou‐Lampoudi et al. reported a prevalence of one of 154 preschool Greek children, while another study conducted in the adult Greek population estimated a prevalence of about one of every 558 . The size of our study group was almost within detection limits according to the prevalence in the paediatric population .…”
Section: Discussionsupporting
confidence: 49%
“…Karagiozoglou‐Lampoudi et al. reported a prevalence of one of 154 preschool Greek children, while another study conducted in the adult Greek population estimated a prevalence of about one of every 558 . The size of our study group was almost within detection limits according to the prevalence in the paediatric population .…”
Section: Discussionsupporting
confidence: 49%
“…The pooled prevalence of biopsy-proven CD ranged from 0.5% (95% CI, 0.2%-0.9%) in Africa 11,31,33,34 to 0.8% (95% CI, 0.6%-1.1%) in Europe. [53][54][55][56][57][58][59][60][61]63,65,66,68,70,71,74,76,77,80,[82][83][84][85][87][88][89][90][91][92][93]115,116 Of 7 studies included in the calculation of seroprevalence from North America, 6,95-100 biopsies were not performed in 4 studies. 95,97,99,100 In 2 other studies only 22.6% and 26.9% seropositive individuals underwent a biopsy and thus could not be included in this part of the analysis.…”
Section: Pooled Global Prevalence Of Celiac Diseasementioning
confidence: 99%
“…Of 57 studies included in the calculation of the pooled prevalence of biopsy-confirmed CD, 43 studies reported a separate pooled prevalence for pediatric and adult CD patients. 10,11,31,33,34,[36][37][38][39][40][41][42]47,48,50,53,56,57,59,61,65,66,68,70,76,77,80,82,83,85,[88][89][90][91][92][93]101,102,105,109,111,116,117 A total of 276 of 40,076 screened adults had CD, providing a pooled prevalence of 0.5% (95% CI, 0.3-0.8). Of 65,957 screened children, 891 children had CD, with a pooled prevalence of 0.9% (95% CI, 0.6-1.3), which was higher than that in adults (P < .001).…”
Section: Difference In the Prevalence Of Biopsy-confirmed Celiac Disementioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27] This rapid whole blood self-TG2-based IgA-class fingertip test uses the patient's own endogenous TG2 found in the erythrocytes of a whole blood sample. When the fingertip blood is hemolyzed, the liberated TG2 forms a complex with circulating autoantibodies, if present in the same sample.…”
Section: Poctmentioning
confidence: 99%